2021
DOI: 10.1111/1759-7714.13846
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factor analysis of patients with small cell lung cancer: Real‐world data from 988 patients

Abstract: Background Small cell lung cancer (SCLC) is characterized by aggressive spread and poor prognosis, but has limited treatment options. Results of prognostic factors from randomized trials on treatment arrangement are conflicting and large‐scale real‐world analysis is lacking. Methods Patients diagnosed SCLC between 2008 and 2018 in Peking University Cancer Hospital were included in this study. Kaplan–Meier methods were adopted, and univariate analysis and multivariate Cox regression models were constructed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
3
22
0
Order By: Relevance
“…Compared to males, females could benefit from chemotherapy, and had longer OS and PFS which coincided with the published studies [24]. Although ECOG was significantly against both OS and PFS in previous studies [25], because of the excellent performance status of LS patients, it did not relate to OS in ours. Additionally, our results indicated that the treatment-related factors of chemotherapy cycles, radiotherapy, and PCI were significantly correlated to the prognosis of LS-SCLC.…”
Section: Discussionsupporting
confidence: 85%
“…Compared to males, females could benefit from chemotherapy, and had longer OS and PFS which coincided with the published studies [24]. Although ECOG was significantly against both OS and PFS in previous studies [25], because of the excellent performance status of LS patients, it did not relate to OS in ours. Additionally, our results indicated that the treatment-related factors of chemotherapy cycles, radiotherapy, and PCI were significantly correlated to the prognosis of LS-SCLC.…”
Section: Discussionsupporting
confidence: 85%
“…These comprehensive biomarkers are developed based on clinical and laboratory parameters, the number of which varied between two and seven. ECOG PS and LDH have been widely accepted as prognostic factors, and both are the parameters most frequently concluded in the scoring system (30,31). PILE is a prognostic candidate score consisting of PIV, LDH, and ECOG PS, which was developed by a simple 0/1 scoring system (for PIV < median = 0, ≥median = 1; for LDH ≤ULN = 0, >ULN = 1; for ECOG PS <2 = 0, ≥2 = 1).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that most clinical trials excluded patients with ECOG PS ≥2, the dramatic underrepresentation of patients with ECOG PS ≥2 makes it difficult to ascertain the real benefit of anti-PD-1/L1 inhibitor in this patient population (27). Moreover, the majority of SCLC patients already have ES disease when they were first diagnosed, in which there were more patients of ECOG PS 2-3 (30). Hence, we decided ECOG PS = 2 as a cutoff value, instead of ECOG PS = 1 reported in the previous literature (24).…”
Section: Discussionmentioning
confidence: 99%
“…Another even more recent and large real‐world study on both LS‐ and ES‐SCLC found that ECOG PS 0–1, response to primary systemic treatment, aggressive RT, and three or more lines of CT were predictive of better OS in the whole group. 21 In the multivariable analysis, more advanced age was not an unfavorable prognostic factor. Even the presence of comorbidities did not have an impact on survival.…”
Section: Discussionmentioning
confidence: 85%